Speaking materials for conversation class at Islamic senior high school - Mujawazah Mujawazah; Agus Widyantoro (Department of Applied Linguistics, Graduate School of Universitas Negeri Yogyakarta, 2019)
This research study aimed to develop English speaking materials to support the learning process in Conversation class of the tenth-graders at Madrasah Aliyah (Islamic senior high school) Al Ma’had An Nur, Bantul. This research was a research and development study. The development was carried out through several steps, namely the needs analysis, a course grid design, product development, product validation, product revisions, try-outs, and final product development. The research had two results. First, it produced a set of speaking materials in the form of printed books. Second, the findings showed that the materials were appropriate to be applied in the Conversation class of the tenth-graders at Madrasah Aliyah Al Ma’had An Nur, Bantul considering the result of the materials evaluation by experts and students’ try-outs. They scored 3.59 and 3.32 for the mean score of the scale 1 to 4 and were categorized as “Very Good”.